Características, cotidiano escolar e percepções dos alunos do curso técnico agrícola integrado ao ensino médio na modalidade alternancia da ETEC de Andradina-SP-Brasil - Pina, Ticiana Petean [UNESP]; Sant'Ana, Antonio Lázaro [UNESP]; Gonzaga, Douglas De Araujo; Pina, Mathues Alexandre Dos Santos [UNESP] (My University, 2017)
This article makes a diagnosis of the young children of seated students of the Technical Course in Agropecuaria Modality Alternation of Etec Andradina (SP), seeking to apprehend the vision of these young people about the School, the pedagogy employed; Their future experiences and intentions. A questionnaire was applied to 15 young people. It was verified that the great majority of the students is satisfied with the modality in alternation, affirms that it applies in the lot of the family great part or almost everything that it learns in the School and they feel prepared for the future.
Characteristics, school daily and student perceptions of the agricultural technical course integrated to the high school in the alternance modality in ETEC of Andradina-SP-BRAZIL
Keywords: Alternation pedagogy; Rural education; Succession; Young people